Experiences of encounters with healthcare professionals through the lenses of families living with chronic illness. Issue 3 (7th December 2017) - Årestedt, Liselott; Persson, Carina; Rämgård, Margareta; Benzein, Eva
Abstract : Aims and objectives: To describe and explore the experience of healthcare encounters in families living with chronic illness. Background: Living with chronic illness is a family concern and often includes frequent encounters with healthcare professionals. These encounters affect how persons with illness and family members handle everyday life. Disease‐related explanations are perceived by healthcare professionals as being of higher importance than the actual experience of illness, even though patients are concerned with issues involving their everyday life. Design: A descriptive design with a qualitative approach. Methods: Narrative family interviews were conducted with twelve families, using a qualitative content analysis. Results: One main category was indicated following analysis, specifically "The impact of an accompanying family member." Additionally, three subcategories were revealed; "The importance of collaboration, " "Mutual understanding, " "A desire to be confirmed in one's illness". Conclusions and relevance to clinical practice: Having a participating family member increased the sense of power in families during encounters with healthcare professionals. This participation constitutes a level of support, making it easier for families to handle everyday life due to illness. Family members are, in most cases, included in discussions and decisions, both before and after encounters, and it should be a natural for healthcare professionals to invite them to the encounter too. This is an offer that may not fit every family, but the person with illness or the family should at least have the opportunity to choose.